Long Non-coding RNA PVT1 as a Prognostic and Therapeutic Target in Pediatric Cancer - Boloix, Ariadna; Masanas, Marc; Jiménez, Carlos; Antonelli, Roberta; Soriano, Aroa; Roma, Josep; Sánchez de Toledo, Josep; Gallego, Soledad; Segura, Miguel F. (Frontiers in Oncology, 2019)
In recent decades, biomedical research has focused on understanding the functionality of the human translated genome, which represents a minor part of all genetic information transcribed from the human genome. However, researchers have become aware of the importance of non-coding RNA species that constitute the vast majority of the transcriptome. In addition to their crucial role in tissue development and homeostasis, The revolution in RNA biology in recent years has spawned a corresponding change in RNA-based strategies to generate new types of therapeutics. Mmounting evidence shows non-coding RNA to be deregulated and functionally contributing to the development and progression of different types of human disease including cancer tumor both in adults and pediatricchildren. Small non-coding RNA (i.e. microRNA) are in the vanguard of these studies clinical research , some of which revealed that RNA could be used as are already in early-phase clinical trials as disease biomarkers or new therapeutic targets. HoweverFurthermore, many more expectations have been raised for long non-coding RNAs, by far the largest fraction of non-coding transcripts, and still fewer findings have been translated into clinical applications. In this review, we center on PVT1, a large and complex long non-coding RNA that usually confers oncogenic properties on different tumor types. We focus on the compilation of early advances in the field of pediatric tumors, which often lags behind clinical improvements in adult tumors, and provide a rationale to continue exploring studying PVT1 as a possible functional contributor to pediatric malignancies and its consideration as a potential prognostic marker or therapeutic target.